(untitled) (Bangladesh Journal of Medical Science, 2025)
According to Global Cancer Statistics (GLOBOCAN 2022), Africa, Europe, and Asia account for up to 90% of all cases of primary liver cancer, with 70.1% of cases occurring on the Asian continent. In the Republic of Kazakhstan in 2023, the incidence of liver cancer was 5.6 per 100,000 population, and the mortality rate was 2.7. Between 2014 and 2023, liver cancer had the lowest five-year survival rate among all malignant neoplasms in Kazakhstan1. Hepatocellular carcinoma (HCC) is the most common malignant tumor of the liver, accounting for up to 85% of all forms of primary cancer2. HCC therapy varies depending on the stage of the disease and includes a variety of clinical strategies: from targeted and immunotherapy to liver transplantation3. Sorafenib remains the main drug for the treatment of HCC4,5, while doxorubicin is used in transarterial chemoembolization of the hepatic artery (TACE)6. However, the use of modern methods of HCC treatment is accompanied by the risk of developing cardiotoxicity 7, leading to cancer therapy-related cardiac dysfunction (CTRCD) 8. However, the use of modern methods of treating GCC is accompanied by the risk of developing cardiotoxicity 7, leading to cancer therapy-related cardiac dysfunction (CTRCD) 8. CTRCD is accompanied by the development of reversible or irreversible, functional or structural changes in the myocardium and manifests itself with symptoms of cardiovascular disease 8,9. Complications that develop during chemotherapy negatively affect both the quality of life and overall survival of patients, regardless of the prognosis associated with the underlying disease 10. Confirmation of cardiotoxicity requires a comprehensive diagnostic approach, including clinical evaluation, electrocardiography (ECG), echocardiography (TTE), and cardiac biomarkers (high-sensitivity troponin (hs-cTn), brain natriuretic peptide (NTproBNP)) 11,12. Among these, TTE (namely global longitudinal strain (GLS) and NTproBNP levels) are the most sensitive tools for diagnosing early preclinical LV dysfunction and monitoring the dynamics of cardiotoxicity13. And considering clinical practicality, sensitivity, and specificity, GLS, hs-cTn, and NT-proBNP are the most preferred diagnostic methods14. Unfortunately, not all laboratories in Kazakhstan are capable of measuring hs-cTn and NT-proBNP levels, and not all cancer centers are equipped with the necessary equipment to detect early markers of myocardial dysfunction, such as GLS. Nevertheless, in recent years there has been a steady trend towards wider implementation of these methods in oncology practice due to their high diagnostic value and improved technical accessibility. Currently, there is extensive data on increased levels of cardiac biomarkers in patients receiving sorafenib and doxorubicin 15-17. In our study, we analyzed changes in laboratory parameters of hs-cTn I and NT-proBNP in patients with HCC receiving targeted therapy and targeted therapy in combination with TACE. The analysis was performed before treatment and 6 months after the start of therapy, both within groups and between groups. MATERIALS AND METHODS The result of the article is a subanalysis in a prospective study performed under grant from the Ministry of Science and High Education of the Republic of Kazakhstan (Individual Registration Number AP19176025). The study was carried out from October 2024 to September 2025. The research was conducted in accordance with the Declaration of Helsinki and was approved by the Ethics Committee of the of nJSC «Astana Medical University» (No. 21 from 09/2023). All participants provided written informed consent prior to enrollment in the study. A total of 69 patients with HCC were included in the study. The patients were divided into two groups based on the treatment protocol. The first group consisted of 29 patients who received daily targeted therapy with sorafenib at a dose of 800 mg per day. The second group included 40 patients who, in addition to receiving sorafenib at the same dose, underwent TACE with doxorubicin at a dose of 50 mg. Exclusion criteria included patients under 18 years of age, those with metastatic liver cancer, other types of malignancies, cardiovascular diseases, any intraventricular conduction abnormalities, heart rhythm disturbances, ejection fraction less than 50% and a glomerular filtration rate (GFR) less than 30 mL/min. All patients underwent laboratory testing (validated equipment from Roche Diagnostics, Mannheim, Germany) of cardiac biomarkers (hs-cTn I и NTproBNP) before the initiation of therapy (4 ± 1 days) and 6 months after the start of treatment. To assess the probability of developing chronic heart failure, a logistic regression model was constructed, where the predictors were indicators of left ventricular systolic function, and the dependent variable was the occurrence of CHF 6 months after the start of target therapy. Equation (a) was constructed to reflect the dependence of the probability of CHF on GLS indicators. The equation was as follows: Р = (а) where P is the theoretical probability of developing CHF 6 months after the start of therapy, z = (FAC in % x 0.938) + (GLS in % x 0.478) + 410.467. The cut-off value in the model was set at 0.2. If, after calculations, P was less than 0.2, the risk of developing CHF was considered to be higher. Statistical analysis was performed using SPSS version 26 (IBM, USA). For variables with a non-normal distribution, non-parametric methods were applied: the Mann–Whitney U test (for intergroup comparisons) and the Wilcoxon test (for intragroup comparisons). For variables with a normal distribution, Student’s t-test was used. Statistical significance was set at p < 0.05. Data are presented as means with standard deviations, and binary variables are presented as frequencies in absolute values and percentages. Ethical approval The study was approved by the Astana Medical University ethics committee RESULTS Table 1 presents the general characteristics of patients receiving both targeted therapy and targeted therapy combined with transarterial chemoembolization (TACE). The total number of patients with hepatocellular carcinoma included in the study was 69. Women prevailed in the targeted therapy group, accounting for 19 people (66%), and in the targeted therapy combined with TACE group, accounting for 23 women (57%). The average age of patients was 57±8.1 and 59±7.7, respectively. Body mass index, hemoglobin, leukocyte, and platelet levels were within normal limits, with no differences between the two groups. Both groups were at stage C2 of GFR (glomerular filtration rate). BJMS, Vol. 24 No. 04 October’25 Page : 1215-1221